(untitled) (Human Factors in Design, 2024)
This study is the result of a master’s search that had aim to evaluate the visual elements of interface design, for the development of a mobile application to aid supermarket purchases, aiming at improving the process of digital inclusion of the elderly public. Initially, the visual elements applied to the prototype were established and subsequently evaluated by the target audience. The results obtained confirmed the suitability of the visual elements used and reinforced the need for greater fomentation of digital inclusion for the elderly public.